Effect of peripheral blood absolute monocyte count at admission on relapse-free survival in patients with idiopathic thrombotic thrombocytopenic purpura in remission - Yu, Xiaomin; Zhong, Mingzhu; Wang, Chen; Shi, Yifen; Xing, Chongyun; Yu, Kang; Lin, Ying; Ou, Rongying; Yang, Junjun; Zhu, Liqing (Frontiers in Medicine, 2024)
IntroductionPeripheral monocytes have been reported to correlate with clinical outcomes in various types of malignancies. Previous reports have also shown that acute-phase thrombotic thrombocytopenic purpura (TTP) plasma could induce the activation of monocytes. However, the significance of peripheral blood absolute monocyte count (AMC) in idiopathic TTP remains an unanswered question. The primary aim of this retrospective study was to evaluate the prognostic value of AMC at admission in idiopathic TTP patients in remission.MethodsA total of 37 patients with idiopathic TTP who survived their first episode of the disease and achieved remission following treatment were eligible for inclusion in the study. SPSS and Stata were used to analysis.ResultsThere were 1 patient (2.7%) with low AMC (< 0.12  × 109/L), 27 patients (73.0%) with normal AMC (0.12–0.80 × 109/L), and 9 patients (24.3%) with high AMC (> 0.80 × 109/L) at admission. Ten (27.0%) of 37 patients in our cohort subsequently relapsed (1 in the low AMC group and 9 in the normal AMC group). Survival analysis showed that there was a trend of higher relapse-free survival (RFS) rate in patients having increased A MC (log-rank test, p = 0.026). Univariate analysis revealed that increased AMC at admission was significantly associated with higher RFS (hazard ratio = 0.12, 95% confidence interval: 0.02–0.62, p = 0.011).DiscussionOur results suggest that increased AMC at admission could represent a predictor of higher RFS in TTP patients having survived their first episode of the disease and achieved remission following treatment.